Prevalence of pulmonary hypertension and associated factors among rheumatic heart disease patients in Ethiopia - Asmamaw Gedefaw; Yihealem Yabebal Ayele; Gebeyaw Wudie; Abiyot Tefera; Agerye Kassa Yirdaw; Tadele Demilew (BMC Cardiovascular Disorders)
Abstract Background In developing countries evidences regarding pulmonary hypertension (PH) in rheumatic heart disease (RHD) patients are lacking, despite being responsible for significant morbidity and mortality. As a result, identifying the factors that influence PH is crucial to improve the quality of care. Objective To determine prevalence of pulmonary hypertension and its associated factors among rheumatic heart disease patients at the public hospitals of Bahir Dar city, Ethiopia. Methods An institution based prospective cross-sectional study was conducted among RHD patients who had follow up at the two public hospitals of Bahir Dar city from January 2022 to December 2023. It involved 310 patients selected by systematic random sampling technique. Pretested, structured, and interviewer-administered questionnaires were used to collect sociodemographic and diseases related parameters.Transthoracic echocardiography by cardiologist was used to assess PH. Data were entered using Epidata Manager version 4.6 and analyzed using SPSS version 27. Multivariate logistic regression analysis was used to identify determinants of PH, considering with a p-value of < 0.05 as statically significant, with a 95% confidence interval. Results The mean systolic pulmonary arterial pressure (sPAP) of the participants was 50.2 mmHg [SD ± 25.0 mmHg]. The prevalence of PH among RHD patients was 56.5% (95% CI 50.9 – 61.9) from which 51.4% had severe PH. Severe mitral valve stenosis (AOR 7.8, 95% CI 2.4–25.7), duration of illness ≥ 3 years (AOR 7.7, 95% CI 2.1–28.5), and diuretics use (AOR 5.6, 95% CI 2.2–14.3) were factors associated with PH. In contrast, valvular intervention (AOR 0.06, 95% CI 0.01–0.29) and LVEF ≥ 50% (AOR 0.14, 95% CI 0.02–0.81) were found to be protective factors. Conclusions The prevalence of PH among RHD patients in Ethiopia is high and it’s associated with delayed presentation & complications. Special attention should be paid to early surgical or percutaneous valvular intervention for those who have indication, before they develop permanent cardiac remodeling and LVFE become reduced. As a result, access to valvular intervention need to be addressed to improve PH related morbidity & mortality among RHD patients in Ethiopia.